Integrative structural biology of Tetrahymena telomerase – insights into catalytic mechanism and interaction at telomeres. (17th March 2016) - Feigon, Juli; Chan, Henry; Jiang, Jiansen
Abstract : Telomerase is a ribonucleoprotein complex that helps maintain telomeres, the physical ends of linear chromosomes. The low cellular levels of telomerase, propensity for telomerase reverse transcriptase and other telomerase proteins to aggregate, and cell cycle regulation of telomerase assembly in most organisms has made it a challenging complex for structural biology. Here we review recent progress in determining the structural basis of Tetrahymena telomerase holoenzyme function and interaction at telomeres from solution NMR, X‐ray crystallography and electron microscopy studies, including the first cryoelectron microscopy structure of a telomerase holoenzyme ( Science, 350, 2015, aab4070). Abstract : We review the first cryoelectron microscopy structure of telomerase, from Tetrahymena. The structure of the TERT‐TER‐catalytic core and the presence of two Replication Protein A like complexes, TEB (Teb1‐Teb2‐Teb3) and CST (p75‐p45‐p19), are revealed. p50 binds TERT like the human telomerase protein TPP1 and tethers TEB and CST. Previously unknown homologies to human telomere binding and telomerase interacting proteins are discussed.